Effect Of Aerobic And Yogic Training On Body Composition Among Sedentary Women Of Manipur - et. al., Loitongbam Baby Sujata Devi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
he current trends of lifestyle purposely makes people suffer from various non communicable diseases . Social barrier was another hindrance in participation. It need to take up several studies to motivate involvement of women. Objective: To assess the effect of aerobic and yogic training on body composition among sedentary women of Manipur.Methods: Forty women of average age 50.07± 6.3 who lead a sedentary lifestyle from Lairikyengbam Leikai, Imphal East District Manipur were randomly minimized into two groups and assigned to aerobic and yoga training respectively . Body weight, Body mass index and Fat percent measurement was obtained before the commencement of training as baseline using bioelectrical impedance analyzer (BIA) methods and after 8 weeks training, the same measurement was taken as final measurements. Analysis and Results: Data was analyzed using SPSS statistical software by running paired t test for each group and then independent t test for comparing between group variables. Data indicates significant decrease in Body weight, Body mass Index and fat percent in both aerobic and Yoga for pretest and posttest compares (p<0.05), Significant difference was observed in between group comparison in body weight and body mass index. No difference was observed in between group comparisons of fat percent (P>0.05), however Cohen’s d shows that aerobic has more effect size than yoga. Conclusion: These findings suggest that both aerobic and yoga can be practices for reduction of bodyweight, body mass index and fat percent